2009
DOI: 10.2178/jsl/1254748693
|View full text |Cite
|
Sign up to set email alerts
|

The strength of the rainbow Ramsey Theorem

Abstract: Abstract. The Rainbow Ramsey Theorem is essentially an "anti-Ramsey" theorem which states that certain types of colorings must be injective on a large subset (rather than constant on a large subset). Surprisingly, this version follows easily from Ramsey's Theorem, even in the weak system RCA 0 of reverse mathematics. We answer the question of the converse implication for pairs, showing that the Rainbow Ramsey Theorem for pairs is in fact strictly weaker than Ramsey's Theorem for pairs over RCA 0 . The separati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(75 citation statements)
references
References 15 publications
1
74
0
Order By: Relevance
“…Then any function f : [ω] n → k has a homogenous set H. Theorem 2 (RRT k n ) Given n, k ∈ ω and a k-bounded function f : [ω] n → ω, there exists a rainbow set R for f. [3] proved that RRT 2 2 is strictly weaker than RT 2 2 under RCA 0 and RRT 2 2 is incomparable with WKL 0 over RCA 0 in 2009. Recently, Wang [8] showed that RRT 3 2 implies neither WKL 0 nor RRT 4 2 under RCA 0 . Theorem 3 (FS(k)) For each function f : [ω] k → ω and k ∈ ω, there is a free set S for f.…”
Section: Introductionmentioning
confidence: 99%
“…Then any function f : [ω] n → k has a homogenous set H. Theorem 2 (RRT k n ) Given n, k ∈ ω and a k-bounded function f : [ω] n → ω, there exists a rainbow set R for f. [3] proved that RRT 2 2 is strictly weaker than RT 2 2 under RCA 0 and RRT 2 2 is incomparable with WKL 0 over RCA 0 in 2009. Recently, Wang [8] showed that RRT 3 2 implies neither WKL 0 nor RRT 4 2 under RCA 0 . Theorem 3 (FS(k)) For each function f : [ω] k → ω and k ∈ ω, there is a free set S for f.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Csima and Mileti [3] studied the effectivity of the Rainbow Ramsey Theorem (for n tuples and k−bounded colorings). Fix numbers n, k. We say that a coloring of n−tuples c : 2 → ω is a recursive k-bounded coloring of pairs and X is a 2-random real, then X computes a rainbow for c. For more details, consult [3] or the discussion in Section 2.…”
Section: Effective Infinitary Combinatoricsmentioning
confidence: 99%
“…The Csima-Mileti Argument in RCA 0 + 2-RAN. We assume that the reader is familiar with [3]. Our main goal in this section is to sketch a proof, in the formal system RCA 0 + 2-RAN, of the theorem of Csima and Mileti [3, Section 3] that says for any recursive 2-bounded coloring of pairs c : [N] 2 → N and any 2-random real X , there is a rainbow R ⊆ N for c that is recursive in X .…”
Section: θ(|τ| τ) and (∀W < |τ|)¬θ(W τ W)mentioning
confidence: 99%
See 2 more Smart Citations